Multimedia in chemical engineering education: Universiti Teknologi Malaysia Experience - Mohd Yusof, Khairiyah; Yunus, Robiah; Yong, Fo Sin; Tan, Boon Seong; Ripin, Adnan; Abdul Aziz, Badhrulhisham (1995)
This paper highlighted the application of multimedia package, called Evaporator Professional that was developed using Authorware Professional. The software was used as part of the reference and teaching material for third year chemical engineering undergraduates. From the survey conducted at the end of the semester, most of the students were satisfied and found the software to be useful.